Efficacy and safety of bridging therapy prior to CAR T-cell therapy in relapsed or refractory multiple myeloma - Marie Christine Wesener; Uta Margareta Demel; Thomas Pabst; Raphael Teipel; Anca-Maria Albici; Bastian Von Tresckow; Marcel Teichert; Amelie Boquoi; Tobias Holderried; Friederike Schmitz; Fabian Müller; Friedrich-Linus Rößiger; et al. (Haematologica, 2026)
Disease burden at the time of BCMA-directed chimeric antigen receptor (CAR) T-cell infusion is a key determinant of outcome in relapsed or refractory multiple myeloma (RRMM). Bridging therapy is frequently administered between leukapheresis and infusion to prevent disease progression, yet its clinical impact remains unclear. We conducted a multicenter real-world cohort study of 399 patients with RRMM treated with BCMA-directed CAR T-cell therapy, including 348 (87%) who received bridging therapy. Bridging therapy recipients had more advanced and biologically adverse disease, including higher rates of high-risk cytogenetics and penta-class refractoriness. Bridging efficacy varied substantially by regimen (P